(untitled) (Journal of the College of Basic Education, 2020)
Differences of statistical significance in visual perception skills among students with learning disabilities and ordinary students. Statistical significance differences in visual perception skills by type. The correlative relationship between visual perception skills and learning difficulties. In order to achieve the objective, a simple random sample was selected from four elementary schools from the first Karkh education schools, consisting of (45) fifth graders who showed signs of learning difficulties according to the system of selection of these students. , And (45) of the ordinary students of the fifth grade students of primary schools of the sample with learning disabilities writing. The researchers built a note form to identify those with learning difficulties in writing in light of the characteristics and indicators of writing disorders consisting of (20) words in the light of a three-dimensional scale determined by the student’s observation (teacher) and extracted the honesty and consistency of the observation form. In order to measure the visual perception, the researchers constructed the visual perception skills test, which consists of seven skills (visual distinction - visual memory - understanding spatial relations - optical stability of the form - optical sequence memory - the relation between the shape and the ground visually - optical closure). Of (10) paragraphs, and extracted the standard characteristics of the skills represented by honesty and consistency. To ascertain the results of the study, the arithmetical averages and standard deviations of the scores of learners with learning difficulties were calculated and normalized for visual perception skills according to each visual perception and test skill as a whole using the TEST for two independent samples. The results of the study showed that there are statistically significant differences between students with learning difficulties writing and normal in all skills of visual perception skills. And that there are differences of statistical significance in the skills of visual perception by gender and for the benefit of females, as well as the search revealed an inverse correlation between the degrees of visual perception skills and degrees of learning difficulties writing.